Lung Health and the Exposome How Environmental Factors Influence Lung Health - Khatri, Sumita B.; Pennington, Emily J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana, 2022)
This book is ideal for the practicing clinician looking to better understand how our environment impacts the lung. A compilation of reviews explores how clinicians can be aware and better determine environmental effects on lung health, and provides guidelines for medical providers to diagnose, counsel and mitigate risk. Various lung diseases are affected by the external environment. Asthma is common, however other airways diseases, such as interstitial lung disease, malignancies, and even adverse effects from reactions treatments for other medical conditions can affect the health of the lungs. While there are books and chapters written on occupational lung disease and environmental causes of asthma, the intent of this body of work is to address the exposome and the effects on a broader group of lung disease. In addition to information on traditional exposure sources, such as air pollution and occupational exposures, this resource explores newer areas of interest, including lung disease from recreational inhalants and the role of climate change on lung health. Written by expert respiratory specialists, the articles cover a wide range of topics, including: How air pollution effects airways disease, including asthma, COPD, and cystic fibrosis Risk factors and effects of indoor mold exposure Both medical and non-medical exposures that increase the risk of or cause interstitial lung disease (ILD) also known as diffuse parenchymal lung disease (DPLD) Acute and chronic lung disease associated with recreational inhalants The epidemiologic and molecular mechanisms of air pollution effects on pulmonary hypertension Climate change and weather-related lung health issues Areas in this field that need further evaluation.
Air Matters: The Effect of Ozone and Traffic Related Air Pollution on the Airways -- Environmental Factors on Lung Health in Cystic Fibrosis and non-Cystic Fibrosis Bronchiectasis -- Molds and Respiratory Disease -- Occupational Exposome and Lung Health -- Environmental and Pollution Related Risks for Hypersensitivity Pneumonitis -- Lung Cancer in Never Smokers -- Acute and Chronic Lung Disease from Recreational Inhalants -- Pulmonary Hypertension and Air Pollution -- Climate Change and the Lung Exposome.
Keywords: Internal medicine; Internal Medicine; Lung Diseases